PROSPECTS AND PROBLEMS IN THE HOTEL AND RESTAURANT BUSINESS IN THE WORLD - Liavynets, Heorhii (SWorld-Ger Conference proceedings, 2024)
Detailing the relevance of this publication, the author emphasizes that the development of the hotel and restaurant business is an important driver of economic growth, job creation and regional development. It supports the expansion of tourism, attracts f